2021
DOI: 10.1177/19322968211032701
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Therapies to Optimize Closed-loop Glucose Control

Abstract: Closed-loop insulin delivery systems are fast becoming the standard of care in the management of type 1 diabetes and have led to significant improvements in diabetes management. Nevertheless, there is still room for improvement for the closed-loop systems to optimize treatment and meet target glycemic control. Adjunct treatments have been introduced as an alternative method to insulin-only treatment methods to overcome diabetes treatment challenges and improve clinical and patient reported outcomes during clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Although those not using these medications also experienced substantial improvements, these results suggest that those using AID in conjunction with GLP-1 RAs and/or SGLT-2 inhibitors may experience greater benefit than those not using these medications; however, additional research is needed to confirm whether this trend is reproducible. These outcomes are not surprising; several studies have already investigated the use of GLP-1 RAs and SGLT-2 inhibitors alongside AID in people with type 1 diabetes, with promising results reported (27)(28)(29).…”
Section: Discussionmentioning
confidence: 97%
“…Although those not using these medications also experienced substantial improvements, these results suggest that those using AID in conjunction with GLP-1 RAs and/or SGLT-2 inhibitors may experience greater benefit than those not using these medications; however, additional research is needed to confirm whether this trend is reproducible. These outcomes are not surprising; several studies have already investigated the use of GLP-1 RAs and SGLT-2 inhibitors alongside AID in people with type 1 diabetes, with promising results reported (27)(28)(29).…”
Section: Discussionmentioning
confidence: 97%
“…Its use is not as extended as those of insulin and glucagon, but it has proven useful in reducing postprandial hyperglycemia, and a 1-year long trial showed that pramlintide significantly helped to reduced HbA1c 4 values (Ratner et al, 2004). Pramlintide was approved for its use in T1D treatment by the FDA (U.S. Food and Drug Administration) in 2005 (Srinivasan et al, 2021). A posterior meta-analysis (Qiao et al, 2017) gathered ten clinical trials with pramlintide from 1997 to 2016, to analyze its efficacy and safety.…”
Section: Pramlintidementioning
confidence: 99%
“…Cardiac risks (Blonde et al, 2022), but fewer side effects than GLP-1 (Ang and Sherr,2017). Used in T2D,but trials in T1D do not show many potential benefits (Drucker et al, 2010;Ang and Sherr, 2017;Srinivasan et al, 2021).…”
Section: Drugmentioning
confidence: 99%
See 2 more Smart Citations